Tahfizh Program Management at Baitul Insan Pesawaran Integrated Islamic Elementary School and Al Banna Integrated Islamic Elementary School South Lampung - Ridho Apriyadi; Ahmad Fauzan; Oki Dermawan (Mataram University, 2026)
Islamic education has a strategic role in shaping the character and personality of students, one of which is through the tahfizh Al-Qur'an program in elementary schools. As public interest in educational institutions that are oriented towards strengthening Qur'anic values increases, it is necessary to manage a planned and systematic tahfizh program so that learning goals can be achieved optimally. However, in practice, there are still various challenges related to the planning, implementation, and evaluation of the tahfizh program. Therefore, this study aims to examine and analyze the management of the tahfizh Al-Qur'an program which includes planning, organizing, implementing, as well as supervision and evaluation at the Baitul Insan Pesawaran Integrated Islamic Elementary School and Al Banna South Lampung Integrated Islamic Elementary School. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies with the research subjects of the principal, tahfizh program coordinators, tahfizh teachers, and homeroom teachers. The results of the study show that the planning of the tahfizh program in the two schools has been systematically prepared through the determination of memorization targets according to the level and ability of the students, the preparation of the tahfizh curriculum, and the arrangement of activity schedules. The organization of the program is carried out with a clear division of tasks and coordination between school elements. The implementation of the tahfizh program is carried out programmatically through the methods of talaqqi, ziyadah, muraja'ah, tasmi', and tahsin, while supervision and evaluation are carried out through monitoring of memorization achievements and periodic evaluation of teacher performance and student development. Overall, the management of the tahfizh program at SDIT Baitul Insan Pesawaran and SDIT Al Banna South Lampung has been running quite effectively and structured in supporting the achievement of students' memorization targets. Nevertheless, it is still necessary to strengthen the aspects of consistency in evaluation and the development of learning method innovations so that the quality of memorization and the sustainability of the program are more optimal. This research is expected to be a reference in the development of the management of the Qur'an tahfizh program in Islamic educational institutions at the elementary school level.